Pengaruh Model Pembelajaran Think Pair Share Mata Pelajaran IPS terhadap Hasil Belajar Siswa Kelas IV di SD Negeri 96 Palembang - Nadia Putriani; Ilham Arvan Junaidi; Masagus Firdaus (Journal on Education, 2024)
It is known that out of 18 students, only 8 students achieved the kkm, while the other 10 students were still below the kkm, so the social studies learning outcomes for class IV students at SD Negeri 96 Palembang were less than satisfactory. So this research intends to test whether there is an influence of the Think Pair Share learning model in social sciences on social science learning outcomes for class IV at SD Negeri 96 Palembang. This research uses a quantitative approach. This research is an experimental research with a Pre-experimental Design type of research whose design is One-Group Pretest-Posttest Design, only consisting of one experimental class and linking two variables, namely the independent variable and the dependent variable, the independent variable is the Think Pair Share learning model. The dependent variable is the result. learn social studies. The subjects of this research were class IV with a total of 18 students at SD Negeri 96 Palembang. Delimitation of subjects in this study used Cluster Random Sampling. The data collection method uses 4 essay questions. Based on the findings obtained, the average pretest score was (35) and after implementing the Think Pair Share learning model, the average increase in the posttest score was (72.78). The results of the t-test obtained a significance value of tcount (15.73) > ttable (2.22) which means that Ho is rejected and Ha is accepted. So it can be concluded that in this research there is an influence of the Think Pair Share learning model on student learning outcomes at SD Negeri 96 Palembang.